A Rebellious Heroine - Bangs, John Kendrick, 1862-1922 (Salt Lake City, UT : Project Gutenberg, 2002)
"A Rebellious Heroine" by John Kendrick Bangs is a novel likely written in the late 19th century. The story centers around a struggling author, Stuart Harley, who is attempting to craft a love story featuring an independent heroine named Marguerite Andrews. However, the tale quickly takes an unexpected turn as Marguerite begins to assert her own will, challenging the conventional narrative tropes laid out by Harley and disrupting his plans for an ideal romance. At the start of the narrative, Harley is introduced as a realist author believing that he must accurately portray life in his writings, drawing inspiration from the very people around him. As he seeks to develop his love story for publication, he plans for Marguerite$1 (Bs journey and encounters aboard a ship. However, Marguerite defies his expectations by missing her appointed departure, leading to a series of amusing complications that disrupt Harley's storyline. Her independent spirit becomes a point of contention, revealing her determination to take ownership of her own narrative and challenging Harley's authority as the author. Thus, the opening portion establishes a dynamic interplay between the creator and his character, setting the stage for a humorous and insightful exploration of storytelling and autonomy. (This is an automatically generated summary.)s
Release date is 2002-07-01
Transcribed from the 1896 Harper and Brothers edition by David Price
Keywords: Authors -- Fiction